FAKTOR-FAKTOR YANG MEMPENGARUHI KURANG PARTISIPASI PRIA PASANGAN USIA SUBUR (PUS) DALAM MEMILIH METODE KONTRASEPSI PRIA DI DESA PAUH TIMUR WILAYAH KERJA PUSKESMAS KOTA PARIAMAN - Ningsih, Mahdalena Prihatin; Rahmawati, Lisa (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
ABSTRACT: Gender equality and justice in KELUARGA BERENCANA (family planning) has been one of the main strategies in the implementation of KB all over the world. Health Ministry policies in an effort to accelerate the decline in AKI basically referring to strategic intervention â€œEmpat Pilar Safe Motherhoodâ€, that is the first pillar KELUARGA BERENCANA. Nowadays the main problem in KB is the low participation rate of male in implementation of KB program and reproduction health. SDKI 2011 results show that the participation of male in following KB was low; 1.3% for condom usage and less than 1% for vasectomy since 1991. Whereas the achievement of KB usage for male in West Sumatera in 2011 is 12% MOP and 64.65% condom. Besides that in Pariaman City 0.47% MOP dan 25.7% condom, the lowest is in Middle Pariaman District 0.69% MOP and 21.3% condom. Low level of male participation in using contraception is influenced by many factors like education, age, social culture, religion, geography, and knowledge about contraception. Research objective: This research is purposed to know about factors that influencing the low level participation of male PUS in selecting Male Contraception Method in PauhTimur Village, Community Health Center (Puskesmas)Pariaman City working area. Research type: Descriptive analytic research with cross sectional approach. The Population is 263 male PUS in PauhTimur Village. The number of sample is 39 male which are taken for random sampling. Data analyze using univariate and bivariate. Research results show that there is correlation of knowledge (p=0.001), social culture (p=0.004), and KB service access (p=0.001) to male PUS participation. Expected by stakeholders in order to improve Education Information Communication (KIE) through counseling or other information related to male contraception to increase the knowledge about contraception. Â Keywords: Participation, Male, Contraception